Phenotypic divergence across populations does not affect habitat selection in an Amazonian poison frog - Martin Mayer; Lia Schlippe Justicia; Bibiana Rojas (Global Ecology and Conservation)
Understanding intraspecific variation in habitat selection by polytypic species, where distinct variants occur in separate populations, can improve our knowledge of population-specific selective pressures and inform conservation measures. Here, we investigated differences in habitat selection across six populations of the dyeing poison frog (Dendrobates tinctorius), an aposematic species characterized by great phenotypic variation. In each population, we recorded the locations and associated habitat of frogs and systematically scored available habitat. We hypothesized that habitat selection differs (1) among populations containing different variants, predicting that larger-bodied frogs are less dependent on moisture-retaining structures; (2) between disturbed and pristine areas, predicting frogs in disturbed areas being more reliant on structural diversity and water bodies; and (3) between males and females, predicting stronger differences in habitat selection in populations with greater sexual size dimorphism. We found little variation in habitat selection among populations or between disturbed and pristine areas but detected strong general patterns across populations. Frogs selected for proximity to tree falls, dead woody material, presence of water pools, and avoided areas with extensive ground vegetation and little canopy cover. Moreover, males tended to show a stronger selection for proximity to water and females stronger selection for tree falls. Combined, our results suggest that in aposematic species, habitat selection might be relatively constant across populations, potentially because of reduced susceptibility to local predation risk. Our findings provide important baseline data regarding the habitat requirements of this emblematic species, which can be relevant for efficient conservation measures in the future.